Cultural categories and Dimensions in Kurikulum Merdeka English Textbooks for Junior High School: A Textbook Analysis - Sofiah, Vivi; Sundari, Hanna; Supeno, Supeno (JADEs Journal of Academia in English Education, 2024)
This research aimed to investigate the cultural categories and dimension inculded in Kurikulum Merdeka English textbook ‘Work in Progress' issued by the Ministry of Education for Senior High School grade ten. The reseacher focus on analyzing the content in form of pictures. Thre are 79 pictres being analized from 6 chapters in total. The cultural categories theory by Chao (2011) and cultural dimension theory by Moran (2001) used to analyzed the cultural content on the book. From the 79 pictures being analyzed, there was 53% included in Universality across Culture (UC), 36% Source Culture (SC), 6% International Culture (IC), 5% intercultural Interaction (ICI), and 0% Target Culture (TC). Meanwhile, for the cultural dimension, 47% were in ‘product dimension, 23% in ‘person' dimension, 21% in ‘practice' dimension, 6% in ‘perspective' dimension, and 3% in ‘community' dimension. The researcher conclude that the English Tetxbook ‘Work in Progress' for Senior High School grade ten need more consideration to the cultural content because it does not have a balance portion of cultural categories and dimension that can affect cultural bias and awarness into students perseption. The study underscores the need for greater attention to cultural content within the "Work in Progress" English textbook.